Correlation between antioxidant activity and total phenolic content with physicochemical parameters of blended extracts of Camellia sinensis - Lucilene Dornelles Mello; Gabriel Porto Quadros (Universidade Estadual de Maringá, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.12615 This paper evaluated the total antioxidant activity (TAA) and the correlation with parameters such as total phenols (FT), total acidity, pH, redox potential (ORP) and conductivity (EC), of commercial teas of Camellia sinensis, single or blended with other plants. The extracts tested were: Camellia sinensis fermented and unfermented, Camellia sinensis with Citrus limonium, Camellia sinensis with Mentha piperita, Camellia sinensis with Prunus persica, Camellia sinensis with Citrus sinensis. All extracts showed high percentages of TAA and were not significantly different by Tukey's test. The correlation matrices indicated that except for the extract of Camellia sinensis with Prunus persica, all the other extracts had statistically significant correlations. Strong correlations were found between TAA and FT, and between pH and FT. The extract of Camellia sinensis with Mentha piperita presented the highest correlation between TAA and FT. The same compounds that influence the pH and ORP may also influence the EC, for almost all teas. For the fermented and unfermented extracts of Camellia sinensis all parameters had been strongly correlated (r > 0.7).